Ответы и объяснения

2012-10-03T15:58:31+04:00

1)  f(x) = 8sin 3x - 3x

     f(-  x) =  8sin 3(-x) - 3(-x) = 8sin (- 3x) + 3x = - 8sin 3x + 3x =

     =  -  (8sin 3x - 3x) = - f(x)

    т.о.  ∀ х   f(-  x) = - f(x)     =>  функция f(x) = 8sin 3x - 3x  нечетная

               х-1                х+1

2)  f(x) = ---------  -   --------  

               х+2               х- 2


                  -х-1                -х+1       -(х+1)            -(х-1) 

      f(-x) = ---------   -       --------   =   ---------       -     --------   =

                  -х+2               -х- 2      -(х-2)            -(х+2)


     х+1                   х-1               х-1                  х+1

---------   -        --------   =   -   (   ---------   -        --------  ) =  - f(x)

     х-2                   х+2              х+2                  х-2

                    т.о.  ∀ х   f(-  x) = - f(x)     =>  функция f(x)   нечетная